Chapter Shifting Times, Converging Futures: Technologies of Writing Beyond Poggio Bracciolini - Ricci, Roberta (Atti, 2020)
Bracciolini's contribution to visual materiality, graphical innovation, and the book trade is the driving force in the development of a new philological turn. This essay explores the textual consciousness that marked the passage to scrupulous criteria of editing and writing, which ultimately indicates and emphasizes the historical dimension of hermeneutical tradition. With a powerful impact on readership and authorship, Bracciolini stands behind this groundbreaking entanglement, as we rethink textual transmission and modern scholarship in this digital age.